Applicability of a green nanocomposite consists of reduced graphene oxide and β-cyclodextrin for electrochemical tracing of methadone in human biofluids validated by international greenness indexes - Sayyed Esmaeil Moradi; Ardeshir Shokrollahi; Faezeh Shahdost-Fard (Heliyon)
Background: Detecting methadone (MET) is crucial due to its severe side effects. Method: Herein, a green nanocomposite based on reduced graphene (rGO) and β-cyclodextrin (β-CD) has been introduced to modify a glassy carbon electrode (GCE) for real-time measurement of MET. This eco-friendly sensing interface has synergistically benefited from both advantages of rGO and β-CD including excellent electron transfer tunneling and surface area enhancement to selectively trap MET based on its shape and size. Significant findings: The developed sensor electrochemically detected MET at 0.8 V in buffer phosphate with a pH value of 7 under a wide linear concentration range (1 μM–830 μM), including a MET concentration level alarmed based on the consumer opioid tolerance according to the WHO's report. The limit of detection and analytical sensitivity values were calculated to be 333.33 nM and 0.0502 μA μM−1. The acceptable performance of the sensor to detect MET in various real human biofluids including serum, urine, and saliva samples, which is a bonus for the real-time and on-site measurement of MET, may open up a route for noninvasive routine tests in clinical samples. Moreover, the greenness profile of this strategy has been well evaluated by two common international metrics.